2015
DOI: 10.1167/15.8.13
|View full text |Cite
|
Sign up to set email alerts
|

Expectations accelerate entry of visual stimuli into awareness

Abstract: How do expectations influence transitions between unconscious and conscious perceptual processing? According to the influential predictive processing framework, perceptual content is determined by predictive models of the causes of sensory signals. On one interpretation, conscious contents arise when predictive models are verified by matching sensory input (minimizing prediction error). On another, conscious contents arise when surprising events falsify current perceptual predictions. Finally, the cognitive im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
131
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(154 citation statements)
references
References 51 publications
19
131
3
1
Order By: Relevance
“…These findings demonstrate that endogenous attentional scope settings can gate the processing of incoming visual input, fundamentally altering the contents of subjective conscious experience. Furthermore, these results are in line with previous research showing that contextual or endogenous factors can facilitate conscious detection of congruent stimuli (Alsius & Munhall, 2013;Gayet, Van der Stigchel, & Paffen, 2014a;Lupyan & Ward, 2013;Pinto et al, 2015;Salomon, Lim, Herbelin, Hesselmann, & Blanke, 2013;. For instance, when observers listened to a sentence, invisible faces with lip movements congruent with the sentence broke from CFS more quickly than faces with incongruent lip movements (Alsius & Munhall, 2013).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings demonstrate that endogenous attentional scope settings can gate the processing of incoming visual input, fundamentally altering the contents of subjective conscious experience. Furthermore, these results are in line with previous research showing that contextual or endogenous factors can facilitate conscious detection of congruent stimuli (Alsius & Munhall, 2013;Gayet, Van der Stigchel, & Paffen, 2014a;Lupyan & Ward, 2013;Pinto et al, 2015;Salomon, Lim, Herbelin, Hesselmann, & Blanke, 2013;. For instance, when observers listened to a sentence, invisible faces with lip movements congruent with the sentence broke from CFS more quickly than faces with incongruent lip movements (Alsius & Munhall, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…For instance, when observers listened to a recording of a sentence, invisible faces with lip movements congruent with the sentence broke from CFS more quickly than faces with incongruent lip movements (Alsius & Munhall, 2013). Furthermore, internally generated expectations have been shown to reduce suppression time for congruent visual images (Pinto, van Gaal, de Lange, Lamme, & Seth, 2015;. Specifically, word cues (e.g., ''face,'' ''house,'' or ''neutral'') presented prior to b-CFS reduced suppression time for congruent images, while also increasing suppression times for incongruent images (Pinto et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another binocular rivalry experiment that relied not on learned associations but on the strong intrinsic physiological goal of hunger (Radel & Clement-Guillotin, 2012) showed that hungry participants showed preferences in bistable perception towards items related to food than non-food. Finally, to test the effects of prior expectations on conscious access, Pinto and colleagues (Pinto, van Gaal, de Lange, Lamme, & Seth, 2015) employed a modified binocular rivalry task, a socalled 'breakthrough against continuous flash suppression' paradigm. In this paradigm, one eye views constantly changing Mondrian-style images (which initially dominate conscious perception), while the other eye views an image of an object.…”
Section: Social Perceptionmentioning
confidence: 99%
“…Support for this notion is provided by studies that have shown that valid predictions increase the speed of conscious access [22][23][24][25][26] into conscious awareness, thereby enabling the switch from a nonconscious to a conscious stimulus representation, instead of just facilitating its cognitive interpretation or its speed of appearance in time.…”
Section: Cc-by-nc-nd 40 International License Not Peer-reviewed) Is mentioning
confidence: 99%